Big leap in China-Africa ties - Ernest Harsch (Africa Renewal, 2007)
Like other African leaders, Ethiopian Prime Minister Meles Zenawi returned home from a three-day summit in Beijing with enthusiastic praise for his hosts and an armful of new economic agreements. More Ethiopian agricultural products would be allowed into China duty-free, he revealed, and China had pledged some 500 mn for various development projects in Ethiopia. “China is an inspiration for all of us,” he added. “What China shows to Africa is that it is indeed possible to turn the corner on economic development.”